On Spec (M) and Separation Axioms Between T-0 and T-1 - (:unkn) unknown (SOUTHEAST ASIAN MATHEMATICAL SOC-SEAMS, 2015)
In this paper, we first introduce the concepts of several separation axioms between the T-0 and T-1 spaces. We also characterize the modules such as the pm - module, m - module, epsilon - module, ES - module, D-module and Y - module. Some new results of the prime spectrum of a module M over a commutative ring R are given.
Keywords: Prime submodule; Prime spectrum; Separation axioms